The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.omtn.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA PVT1 Promotes Cell Proliferation and Migration by Silencing ANGPTL4 Expression in Cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is the most common biliary tract malignancy, with a low survival rate and limited treatment options. Long non-coding RNAs (lncRNAs) have recently been verified to have significant regulatory functions in many kinds of human cancers. It was discovered in this study that the lncRNA PVT1, whose expression is significantly elevated in CCA, could be a molecular marker of CCA. Experiments indicated that PVT1 knockdown greatly inhibited cell migration and proliferation in vitro and in vivo. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 43 publications
1
57
0
Order By: Relevance
“…Recently, lncRNAs have gained great attention as its role in CCA 15 . Several known lncRNAs were reported to be dysregulated in CCA tissues and involved in the CCA development and progression, such as DANCR 16 , PVT1 17 , and RMRP 18 . Recent studies have reported that SNHG6 is highly expressed in variety of cancer tissues (except CCA) and .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, lncRNAs have gained great attention as its role in CCA 15 . Several known lncRNAs were reported to be dysregulated in CCA tissues and involved in the CCA development and progression, such as DANCR 16 , PVT1 17 , and RMRP 18 . Recent studies have reported that SNHG6 is highly expressed in variety of cancer tissues (except CCA) and .…”
Section: Discussionmentioning
confidence: 99%
“…APOC1P1, PVT1) possibly regulating inflammation and oxidative stress in malignant cholangiocytes 10,11 . Notably, pvt1 oncogene (PVT1) was shown to promote cell proliferation and migration by epigenetically silencing angiopoietin like 4 (ANGPTL4), a tumor suppressor gene candidate 12 . Cyclin dependent kinase inhibitor 1A (CDKN1A), another well-described tumor suppressor gene, was shown to be epigenetically silenced in CCA through the interaction of small nucleolar RNA host gene 1 (SNHG1) lncRNA with enhancer of zeste 2 (EZH2), the catalytic subunit of the polycomb repressive complex 2 (PRC2) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that SPRY4-IT1 exhibits tremendous potentiality for the diagnosis and treatment of CCA and likely functions as a novel diagnostic biomarker and intervention target. experiment was also conducted to prove its carcinogenic function (Han et al, 2018;Yu, W. D. et al, 2018;Yu, Y. et al, 2018aYu, Y. et al, , 2018b. Similar to the above, small nucleolar RNA host gene 1 (SNHG1), which is situated at 11q12.3 region of the human chromosome Zhang, D. et al, 2018;Zhang, R. et al, 2018;, was also verified highly expressed in both CCA tissues and cells.…”
mentioning
confidence: 73%